How can natural hybridisation between self‐compatible and self‐incompatible species be bidirectional?. (1st July 2019) - Li, C; Cousens, R D; Mesgaran, M B
Summary: Self‐compatible (SC) plants often deposit pollen on their own stigmas before flowers open. Thus, if we find natural hybrids between a SC species and a closely related self‐incompatible (SI) species, the pollen donor is usually expected to be the SC species. However, in previous studies of naturally occurring mixed populations of invasive Cakile maritima (SI) and Cakile edentula (SC) in Australia, hybridisation was found to have been bidirectional. Here, we explored the floral development of these species in order to test the hypothesis that there might be a short opportunity for pollinators to visit open SC flowers before the self‐pollen is released. Results indicated that both species showed reverse herkogamy during early development, though by the time pollen was ripe the four long anthers always overtopped the stigma; in C. maritima, most of the short anthers remained below the stigma. In both species, ripe, compatible pollen was able to germinate on the stigmatic surface at all stages of floral development. Anther dehiscence commenced earlier in C. edentula and well before flowers opened, in contrast to C. maritim a, but the timing of pollen release varied between individual flowers, with a small proportion of uncontaminated stigmas after flowering; therefore, C. edentula can be either pollen recipient or pollen donor when interspecific outcrossing occurs. In summary, our results suggest that the variation between individual flowers of C. edentula contributed to the bidirectional hybridisation despite being a predominant selfer, providing new insights into plant colonisation.